2017
DOI: 10.1038/s41598-017-02299-7
|View full text |Cite
|
Sign up to set email alerts
|

Association of SIX1/SIX6 locus polymorphisms with regional circumpapillary retinal nerve fibre layer thickness: The Nagahama study

Abstract: SIX1 and SIX6 are glaucoma susceptibility genes. Previous reports indicate that the single nucleotide polymorphism (SNP) rs33912345 in SIX6 is associated with inferior circumpapillary retinal nerve fibre layer (cpRNFL) thickness (cpRNFLT). Although the region of visual field defect in glaucoma patients is directly related to cpRNFL thinning, a detailed sector analysis has not been performed in genetic association studies. In the present study, we evaluated 26 tagging SNPs in the SIX1/SIX6 locus ±50 kb region i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 41 publications
3
11
0
Order By: Relevance
“…SNP rs10483727 was the first SIX1-SIX6 SNP identified with POAG association, 14,31 and rs33912345 was more frequently investigated in recent studies. 23,37,39 SNP rs10483727 is located in the intergenic region between SIX1 and SIX6, whereas rs33912345 is a missense variant (p.His141Asn) in SIX6. The two SNPs are in strong linkage disequilibrium (LD) (R 2 > 0.96; 1000 Genomes Project Phase 3 v5, provided in the public domain and accessed from http://www.internationalgenome.…”
Section: Discussionmentioning
confidence: 99%
“…SNP rs10483727 was the first SIX1-SIX6 SNP identified with POAG association, 14,31 and rs33912345 was more frequently investigated in recent studies. 23,37,39 SNP rs10483727 is located in the intergenic region between SIX1 and SIX6, whereas rs33912345 is a missense variant (p.His141Asn) in SIX6. The two SNPs are in strong linkage disequilibrium (LD) (R 2 > 0.96; 1000 Genomes Project Phase 3 v5, provided in the public domain and accessed from http://www.internationalgenome.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the case of POAG and SIX1/SIX6, it is not known when these genetic variants start exerting their effects 24 . Studies have reported that individuals with risk allele in SIX1/SIX6 are more susceptible to glaucoma 1,3,25 and have thinner RNFL [20][21][22][23] . Note that these RNFL studies were conducted in older individuals, hence it is not clear whether thinner RNFL found in the older individuals with SIX1/SIX6 variants is due to these individuals being born with thinner RNFLs or due to a faster rate of RNFL degeneration as they age.…”
Section: Discussionmentioning
confidence: 99%
“…www.nature.com/scientificreports/ in the Japanese study 22 . In rs10483727, an European cohort study reported significant global RNFL thinning with each copy of the risk allele as well as the inferior and superior sectors 23 but the study cohort contained a large portion of glaucoma cases and suspects (~ 80%).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although these polymorphisms have never been studied before in relation to congenital cataract and microphthalmia, they have been studied/associated with other disease phenotypes such as BMP4 -V152A with tooth agenesis,[ 30 31 ] cleft lip,[ 32 33 ] and cutaneous melanoma,[ 34 ] and SIX6 - H141N with primary-open angle glaucoma. [ 35 36 37 ]…”
Section: Discussionmentioning
confidence: 99%